PM2.5-induced oxidative stress upregulates PLA2R expression in the lung and is involved in the pathogenesis of membranous nephropathy through extracellular vesicles - Zhang, Wang; Chen, Jiating; Yuan, Ye; Luo, Jiao; Zhou, Zhanmei; Wang, Guobao (Frontiers in Pharmacology, 2024)
BackgroundParticulate matter (PM2.5) has been implicated in the development of membranous nephropathy (MN), but the underlying mechanism has yet to be fully understood. Oxidative stress is an essential factor of PM2.5-related toxicity and plays a significant role in the exposure of target antigenic epitopes in MN. This study aims to explore the pathogenic effects of PM2.5 in facilitating the crosstalk between the lung and kidney in MN.MethodWe examined oxidative stress indicators and the circulating levels of extracellular vesicles (EVs) in patients diagnosed with MN. Additionally, we assessed the expression of M-type phospholipase A2 receptor (PLA2R) in human lung tissue ex vivo. To verify the impact of PM2.5 on PLA2R expression in the lung and the kidney, we stimulated human bronchial epithelial cells (Beas-2B) with lipopolysaccharide (LPS) or PM2.5. We then treated podocytes in vitro with the supernatants from PM2.5-exposed Beas-2B cells, intervening with GW4869, an inhibitor of EV release, to explore the role of EV-mediated cell-cell interactions.ResultsWe found that elevated serum markers of oxidative stress and increased levels of PLA2R + EVs correlated positively with anti-PLA2R antibody levels in the serum of patients with idiopathic MN (IMN). Notably, PLA2R expression was significantly higher in the lung tissue of smokers, suggesting a possible link between PLA2R and oxidative stress. In vitro experiments demonstrated that PLA2R expression in Beas-2B cells was upregulated upon stimulation with LPS and PM2.5, an effect that could be reversed by the antioxidant glutathione (GSH). Furthermore, the supernatants from PM2.5-exposed Beas-2B cells were found to induce PLA2R overexpression and injury in podocytes, with this effect being mitigated by GW4869, an inhibitor of EVs release.ConclusionOur study contributes new knowledge to the understanding of how environmental pollutants, such as PM2.5, cause kidney damage through oxidative stress and EV-mediated signaling. The findings pave the way for further research into therapeutic strategies targeting oxidative stress and EVs, which could potentially improve patient outcomes of MN, particularly in high-risk populations like smokers and those exposed to air pollution.